A nanoconfined iron(iii) fluoride cathode in a NaDFOB electrolyte: towards high-performance sodium-ion batteries. Issue 7 (7th February 2020) - Sun, Zifei; Fu, Wenbin; Liu, Michael. Z.; Lu, Peilin; Zhao, Enbo; Magasinski, Alexandre; Liu, Mengting; Luo, Shunrui; McDaniel, Jesse; Yushin, Gleb
Abstract : Iron(iii ) fluoride (FeF3 ) is considered a potential cathode for sodium-ion batteries (SIBs) due to its high capacity and low cost. Abstract : Iron(iii ) fluoride (FeF3 ) is considered a potential cathode for sodium-ion batteries (SIBs) due to its high capacity and low cost. However, particle pulverization upon cycling generally results in rapid degradation of its structure and capacity. Here, we introduce a free-standing nanoconfined FeF3 cathode and a novel electrolyte salt, sodium-difluoro(oxalato)borate (NaDFOB), for SIBs. The assembled cells show a high discharge capacity up to ∼230 mA h g −1 at a rate of 20 mA g −1 (∼200 mA h g −1 at 100 mA g −1 ) and a capacity retention up to ∼70% after 100 cycles, which represent the best results reported for FeF3 in Na-ion electrolytes. The achieved high performance can be attributed to the synergic protection provided by the nanoconfined FeF3 electrode and the NaDFOB electrolyte. Post-mortem analysis and quantum mechanics show that DFOB anions facilitated the formation of a thin cathode electrolyte interphase (CEI) on the surface of FeF3 -carbon nanofibers (CNFs) via oligomerization.